Hubungan Antara Keamanan Protein, Energi, Dan Vitamin A Terhadap Status Gizi Siswa Baru Sekolah Dasar Di Pantai Lasiana Kota Kupang - Beatrix Soi (JURNAL INFO KESEHATAN, 2017)
A child growth describes the development of nutrition balance between intake and need of nutrition for various biological processes includes for his/her growth. Nutrition intake such as energy, protein, and vitamin A are influential components of one’s nutrition status. Families from low economic level are generally facing malnutrition problems. Coastal areas tend to be identic with fisherman villages and are supposed to have higher protein intake in comparison to highlands areas due to high animal (fish) protein intakes. However, a lot of fisherman villages are also identic to poverty and under-developed areas. The poverty influences children nutrition status. Lasiana beach is one of the coastal areas lies at the border of Kupang city and Kupang regency. The recent study aims at finding out the relation among the Intake of Protein, Energy and Vitamin A to nutrition status of new students of the elementary school at Lasiana coastal areas of Kupang, East Nusa Tenggara Province. The study is quantitative in nature and was carried out using an observational cross-sectional method for one whole month (October 27th – November 27th, 2015). The population is 561 elementary students (SD) located at Lasiana Beach. The sample is 95 students which are taken by means of the proportional random sampling technique. Data analysis is carried out in terms of univariate, bivariate and multivariate respectively. Chi-Square is then used to find out the relationships among variables. It is found out that: among the observed independent variables (parents’ schooling, energy intake, protein intake, and vitamin A intake) only energy, protein, and vitamin A intakes have significant relation with nutrition status of new students of elementary school. These are shown by their <0,05 P values. While parents’ schooling does not have any significant relation.